DIGITAL LINGUISTIC CREATIVITY (DLC) IN INDONESIAN GEN Z INSTAGRAM CAPTIONS: A SOCIOLINGUISTIC ANALYSIS - Balqis Fadila Rahma Sandra; Dedy Subandowo; Amirudin Latif (English Review: Journal of English Education, 2026)
Indonesian Generation Z (Gen Z), born between 1997 and 2012, grows up in the era of digital platforms shows creative linguistic patterns for using English and communicative interaction. This study investigates the distribution of Digital Linguistic Creativities (DLC) captions, which comprise orthographic, lexical, morphological, and semiotic categories, from 124 Indonesian Gen Z Instagram users whereby the DLC captions function as sociolinguistic resources for identity construction and stance taking to interpret sociolinguistic landscape as well.  Employing descriptive qualitative design, this study examines the phenomena which relies on text and image by analysing 124 captions posted from 2025 to 2026.  The findings show that the most frequent captions are orthographic creativities (43%), followed by lexical creativities (30%) that are the second most frequent captions, followed by semiotic creativities (25%) that are the third most frequent captions, and the least frequent captions are morphological creativities (2%). Orthographic creativity becomes the most frequent captions posts because of various linguistic patterns to attract particular attention. Meanwhile, morphological creativity becomes the least frequent captions posts due to the need of word formation analysis. With regard to sociolinguistic landscape, the finding of identity construction reveals that the existence of Instagram users in their online communities is not merely as personal identity but also group identity. The finding of stance taking that includes epistemic and affective stance reveals that Instagram captions posts are created based on knowledge driven-action, inter subjectivity, and emotional expression.